1997
DOI: 10.1098/rspb.1997.0247
|View full text |Cite
|
Sign up to set email alerts
|

The temporal dynamics of reading: a PET study

Abstract: The temporal dynamics of evoked brain responses are normally characterized using electrophysiological techniques but the positron emission tomography study presented here revealed a temporal aspect of reading by correlating the duration a word remained in the visual ¢eld with evoked haemodynamic response. Three distinct types of e¡ects were observed: in visual processing areas, there were linear increases in activity with duration suggesting that visual processing endures throughout the time the stimulus remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 29 publications
(24 reference statements)
5
19
0
Order By: Relevance
“…These regions showed a greater signal for longer durations, similar to other findings in the literature (Grill-Spector, Kushnir, Hendler, & Malach, 2000;Madden et al, 2002;Price & Friston, 1997;Price, Moore, & Frackowiak, 1996;Price et al, 1994). Given that these regions were not sensitive to the SS manipulation, we conclude that they are not directly involved in processing object structure.…”
Section: Occipital and Posterior Fusiform Regionssupporting
confidence: 89%
“…These regions showed a greater signal for longer durations, similar to other findings in the literature (Grill-Spector, Kushnir, Hendler, & Malach, 2000;Madden et al, 2002;Price & Friston, 1997;Price, Moore, & Frackowiak, 1996;Price et al, 1994). Given that these regions were not sensitive to the SS manipulation, we conclude that they are not directly involved in processing object structure.…”
Section: Occipital and Posterior Fusiform Regionssupporting
confidence: 89%
“…Previous studies reported that neural responses of only a few areas within the occipito-temporal cortex increased linearly with visibility or presentation duration of written input (Ben-Shachar et al, 2007;Price and Friston, 1997;Vagharchakian et al, 2012). Here, we found a linear activation pattern in all of the areas identified in the network described above.…”
Section: Stimulus-driven Activation Of Orthographic Phonological Andsupporting
confidence: 75%
“…Thus, the conclusion obtained in the studies using auditory stimuli remains valid even when the activation of the auditory system is elicited by visual input. Although this specific activation profile obtain in the post FUS and STG is more compatible with the idea that top-down information does not contribute to information processing in lower-level language areas, the current data set does not allow us to rule out the possibility that the activation profile may evolve over time (Price and Friston, 1997) and the impact of task demands may be delayed and become detectable only later on.…”
Section: Task-driven Activation Of Orthographic Phonological and Semmentioning
confidence: 81%
See 1 more Smart Citation
“…This three-way interaction between task (visual -manual vs. naming), mapping rule, and region was significant ( p < .03). In hindsight, this difference makes sense because the pIPS (extending into the SPL and the precuneus) is typically engaged during spatial processing ( Berman et al, 1999;Labar et al, 1999;Culham et al, 1998) while the frontal opercular/insular region falls in the vicinity of Broca's area which has been implicated in linguistic processing (Friederici, Meyer, & von Cramon, 2000;Price & Friston, 1997) and tongue movement (Corfield et al, 1999). Thus, RS based on different tasks may not induce identical activation in all ROIs.…”
Section: Differences Among the Roismentioning
confidence: 99%